Social Cycling: Critical Mass Through a Mobile App - García-Herrera, Rodrigo; García-Meneses, Paola Massyel (Frontiers in Sustainable Cities, 2020)
Design and partial implementation of a mobile application that helps bicycle riders flock with other riders while commuting, thus benefiting from the emergent critical mass. Simulations are run to test the model, analysis of their results suggest flock formation is likely given enough users.